The shallow-water Asellota (Crustacea: Isopoda) from the Beagle Channel: Preliminary taxonomic and zoogeographical results - Brenda Lía Doti; Daniel Roccatagliata; Diego Gabriel Zelaya (Scientia Marina, 2005)
The shallow-water Asellota from the Beagle Channel were investigated, based on material collected at four localities in 2001-2002. A total of 3,124 asellotes were sorted, and three new species and 12 new records of distribution were reported. The Paramunnidae showed the highest species diversity and abundance (11 species and 1,463 specimens). The present research raises the number of species known from the Beagle Channel to 23; of these, 16 were previously reported from the Magellan Straits, representing 69% of similarity. Based on the present results and published data, the faunistic affinities for the shallow-water Asellota was 30% between the Magellan region and the Scotia Arc, and 26% between the Magellan region and the Antarctic Peninsula.